Lack of legal order of franchise agreement on business, Perú 2013 - Torres-Torres, Margarita E. (2019)
The aim of the study was to explain the legal uncertainty in the business, due to lack of legislation of the franchise agreement in Peru ; correlational descriptive research, the population was composed of 51 people with Business Contact franchise agreement of Perú, in 2013 ; the same that was used as a sample. An index interview were used in data collection. For the inferential analysis, the chi-square test was used for a sample. From the results, it was found that 52.9% (27 contact persons) mentioned that there is a medium level of certainty in the franchise agreement. Also, 82.4% (42 contact persons ) indicated that there is greater legal certainty when the franchise joined the Peruvian commercial code and 88.2% (45 contact persons ) considered improvements to be implemented for a given standard franchise agreement , all with statistical significance (P ≤ 0.05). Concluding that the lack of legal system of the franchise agreement, produce legal uncertainty in the business of Perú.